2010
DOI: 10.1007/s12243-010-0227-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance of voice over WLANs (VoWLANs) with differentiated services

Abstract: Several technical issues make commercial and large voice over wireless local area network (VoWLAN) services difficult to provide. The most challenging issue when voice over Internet Protocol (VoIP) services are ran over IEEE 802.11-based WLANs is the bandwidth inef f iciency due to the considerable overhead associated with WLAN packet transmission. In this work, we propose a session-based quality-of-service management architecture (SQoSMA) to overcome the low number of VoIP calls in IEEE 802.11 Wireless LANs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Capacity estimates for both the experimental and simulated network were 15 calls for 64 kb/s CBR VoIP traffic and 38 calls for VBR VoIP traffic with a packetization interval of 20ms and an activity ratio of 0.39 respectively. A quality of service management architecture that is session-based was proposed by Badis Tebbani et al [12] to accommodate for the low capacity of VoIP calls in an IEEE 802.11 wireless local area network as well as resolve the issues that occur when new calls are added to a network that has reached its capacity. Several researchers have studied the throughput and traffic generation parameters of an 802.11 wireless local area network [13] [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Capacity estimates for both the experimental and simulated network were 15 calls for 64 kb/s CBR VoIP traffic and 38 calls for VBR VoIP traffic with a packetization interval of 20ms and an activity ratio of 0.39 respectively. A quality of service management architecture that is session-based was proposed by Badis Tebbani et al [12] to accommodate for the low capacity of VoIP calls in an IEEE 802.11 wireless local area network as well as resolve the issues that occur when new calls are added to a network that has reached its capacity. Several researchers have studied the throughput and traffic generation parameters of an 802.11 wireless local area network [13] [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To succeed in dealing with the severe problems of VoIP calls over WiFi while approaching the WiFi capacity limit and congestion, a new scheme, the Quality Assurance of Voice over WLANs (SQoSMA) [16] was proposed. SQoSMA took the approach of incorporating the data with the control and planes for detecting and mitigating congestion events.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study over High Speed Packet Access (HSPA) [15] has shown that not all VoIP implementations are the same as they have differing quality effects on the voice. A strategy used to overcome the quality problems of congestion in WiFi when using VoIP is known as SQoSMA (Session-based Quality-of-Service Management Architecture), Quality Assurance of Voice over WLANs [17]. SQoSMA tries to overcome the bandwidth limitation problems by combining the control and data planes in order to mitigate congestion events by choosing the lowest bitrate adaptive audio codec.…”
Section: Literature Reviewmentioning
confidence: 99%